Organizational Management Implementation in Jumat Berjihat Activities as Student Character Education - Mayasafira, Sarrah Dwiananda (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This research aims to examine the implementation of the organizational management of the "JUMAT BERJIHAT" character education program at SMP Negeri 1 Turi, Lamongan, where the existence of this program was motivated by the phenomenon of juvenile delinquency cases. This research uses descriptive qualitative methods and is strengthened by management theory by James A. F. Stoner and Charles Wankel. The results of this research show that the character education program "JUMAT BERJIHAT" at SMP Negeri 1 Turi, Lamongan, runs smoothly. The students are thrilled with this program because it can improve the religious spirit, and the parents are also happy because there are positive changes in their children and teachers. Teachers at SMP Negeri 1 Turi, Lamongan, were very united in participating in this activity. However, initially, the students at SMP Negeri 1 Turi, Lamongan, still needed to get used to this activity, but now they are enthusiastic about this program. Organizational management has also been implemented with a process structure of planning, organizing, leadership and controlling organizational efforts and the use of all other organizational resources to achieve organizational goals.